PENYUAPAN TERHADAP KOMISIONER KOMISI PEMILIHAN UMUM (KPU) DALAM HAL PENGGANTIAN ANTAR WAKTU (PAW) ANGGOTA DEWAN PERWAKILAN RAKYAT (DPR) (Studi Kasus Wahyu Setiawan) - muhammad gema ramadhan susetiobekti (Dinamika, 2020)
ABSTRACTInterim Replacement (PAW) legislative members (DPR / DPRD / DPD) are common. A board member can be replaced for various reasons in the middle of his term of office. From this explanation, it can be drawn, the formulation of the problem consisting of What is the function of the General Election Commission (KPU) in terms of Inter-Time Replacement (PAW), as well as What are the legal consequences for the commissioners of the General Election Commission (KPU) who commit criminal acts in the determination of Inter-Time Replacement (KPU) PAW). This study recognizes and analyzes the function of the General Elections Commission (KPU) due to the legal consequences for the commissioners of the General Elections Commission (KPU) who commit crimes. This research uses normative juridical research. From the results of this study it can be concluded that the function of the General Election Commission (KPU) in the case of Inter-Time Replacement (PAW) as an administrative function. The legal consequences for KPU commissioners who commit crimes are individual responsibility rather than institutional for the KPU.Keywords: bribery, replacement between time ABSTRAKPenggantian Antar Waktu (PAW) anggota legislatif (DPR/DPRD/DPD) adalah hal lazim. Seorang anggota dewan bisa diganti dengan berbagai alasan di tengah masa jabatannya. Dari penjelasan tersebut dapat diambil, rumusan masalah yang terdiri atas Apa fungsi Komisi Pemilihan Umum (KPU) dalam hal Penggantian Antar Waktu (PAW), serta Apa akibat hukum bagi komisioner Komisi Pemilihan Umum (KPU) yang melakukan tindak pidana dalam penetapan Penggantian Antar Waktu (PAW). Penelitian ini mengetahui dan menganlisa fungsi Komisi Pemilihan Umum (KPU) akibat hukum bagi komisioner Komisi Pemilihan Umum (KPU) yang melakukan tindak pidana. Penelitian ini menggunakan penelitian yuridis normatif. Dari hasil penelitian ini dapat di simpulkan bahwa fungsi Komisi Pemilihan Umum (KPU) dalam hal Penggantian Antar Waktu (PAW) sebagai fungsi administratif. Akibat hukum bagi komisioner KPU yang melakukan tindak pidana perbuatannya menjadi tanggung jawab individu bukan untuk kelembagaan bagi KPU.Kata Kunci: penyuapan, penggantian antar waktu